The contribution of Joseph Schumpeter to economics : economic development and institutional change - Arena, Richard; Dangel-Hagnauer, Cécile. (London : Routledge, 2002)
This collection constitutes an examination of Schumpeter's legacy that is wider than any yet attempted. As one of the key economists of the twentieth century, Schumpeter's economics is viewed in the context of its relation to purer Austrian theories of the free market, Keynesian macroeconomics, the early neoclassicism of Marshall and Walras, and a persuasive argument made for its centrality to the discipline as a whole.
.Includes bibliographical references and index
oif 04/02/14
Loan
Keywords: Schumpeter, Joseph Alois; Economic analysis; Economic development and social change; Enterprenuership; Money, banking and finance